The Novel Serum Biomarkers for Real-Time Treatment Monitoring and Prognostication in Hepatocellular Carcinoma Patients: des-gamma-carboxy prothrombin (DCP), Golgi protein 73 (GP73), osteopontin (OPN), heat shock protein 70 , and NLR in HCC - Wang, Jing; Yang, Qing; Zhao, Lei; Feng, Yiming (Journal of Medical Biochemistry, 2026)
Background: Alpha-fetoprotein (AFP) has limited utility for real-time monitoring of hepatocellular carcinoma (HCC) during locoregional and systemic therapies. We evaluated six novel serum biomarkers—circulating tumor DNA (ctDNA), des-gamma-carboxy prothrombin (DCP), Golgi protein 73 (GP73), osteopontin (OPN), heat shock protein 70 (HSP70), and neutrophil-to-lymphocyte ratio (NLR)—against AFP for post-treatment response assessment and prognostication following transarterial chemoembolization (TACE) and sorafenib. Methods: A prospective cohort of 148 patients with intermediate-stage HCC undergoing TACE (n=86) or sorafenib (n=62) was enrolled. Serum samples were collected at baseline, week 4, week 8, and at radiologic progression. Biomarker kinetics were correlated with mRECIST response and overall survival (OS). Area under the receiver operating characteristic curve (AUC) was calculated for residual disease detection and progression prediction. Results: For post-TACE residual disease detection, HSP70 showed the highest sensitivity (88%), followed by GP73 (84%). For sorafenib monitoring, DCP and OPN independently predicted progression (AUC 0.86 and 0.83 respectively). A composite panel (DCP + GP73 + OPN + HSP70) achieved 92% specificity for early progression detection (AUC 0.93). Patients with persistent elevation of ≥3 markers at week 8 had significantly worse median OS (6.2 vs. 16.8 months, p<0.001). Conclusion: Novel serum biomarkers—particularly DCP for sorafenib monitoring, HSP70 and GP73 for post-TACE residual disease detection, and OPN for tumor burden tracking—enable effective real-time treatment monitoring and prognostication in HCC, outperforming AFP across multiple therapeutic contexts.